Pengaruh Tingkat Pemberian Pakan Buatan Berbahan Dasar Tepung Daun Kelor (Moringa oleifera) Terhadap Kecerahan Warna Ikan Mas Koi (Cyprinus carpio) - Putri Zulvia Suleman Husain; Rully Tuiyo; Juliana (Research Review: Jurnal Ilmiah Multidisiplin, 2023)
One way to improve color quality is by feed nutrition engineering. This study aimed to determine the effect of the level of artificial feeding made from moringa (Moringa olefera) leaf flour on the color brightnees level of koi crap. The material used was moringa leaf flour, wich contains protein and caratenoids that can increase fishs color brightnees and growth. The study employed an experimental method using a completely randomized design with four treartments and three replications. Furthermore, the treatments consisted of treatments A (5%); treatment B  (10%); treatment C  (15%); and treatment D (20%). The stocking density was ten fish/aquarium, and the feeding frequency was twice daily. The findings indicated that the provision of moringa leaf flour as the main igredient of artificial feed had a significant effect (p< 0.05) on color improvement and a highly significant effect (p<0.01) on weight gain. Moreover, the result signified that the highest increase in color was in treatment C from 11.69 to 16.95, the highest increase in absolute length growht was in treatment C with a value of 1.35 cm, and the highest increase in absolute weight gain was in treatment C manely 2,29 gr.